The political consequences of conditional multilateral aid, provided by the International Monetary Fund, for the states of Southern Africa - Roos, Johannes Christiaan (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1994.